2020
DOI: 10.4236/ojtr.2020.83004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Care Therapy on Reducing the Conversion Rate from MCI to Dementia and Role of COVID-19 as Non-Pharmacotherapy

Abstract: Dementia needs to be addressed by various researchers to reduce the risk of morbidity and progression. And dementia was regarded as one of lifestyle-related diseases, and it is estimated that about 10% of MCI (Mild cognitive impairment) progresses to dementia in one year. In this study, we examined whether hand care therapy (HCT) as one of passive horticultural therapy was effective in preventing dementia/MCI. In result, the use of HCT was shown to be effective in preventing dementia and MCI illness and slowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…From the perspective of preventing the conversion from MCI to dementia, the effectiveness of HCT was applied to cognitive impairment, iADL, and senile depression during the period from I (BL: August 2019) to VII (18M: February 2020). In the results, the use of HCT was shown to be effective in preventing dementia and MCI illness and slowing progression [16].…”
Section: Introductionmentioning
confidence: 97%
“…From the perspective of preventing the conversion from MCI to dementia, the effectiveness of HCT was applied to cognitive impairment, iADL, and senile depression during the period from I (BL: August 2019) to VII (18M: February 2020). In the results, the use of HCT was shown to be effective in preventing dementia and MCI illness and slowing progression [16].…”
Section: Introductionmentioning
confidence: 97%
“…Changes appeared in muscle tension, skin conductance and pulse that correlates with reduced blood pressure [4] [5]. Various studies of horticultural therapy programs have demonstrated the positive effects on dementia protection, schizophrenic behavior and those suffering from depression [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…These horticultural therapy activities were passive such as garden appreciation, "hand care treatment and brain rejuvenation aroma", which were less likely to be rejected and more share pleasant feelings [9]. In addition, active functional recovery training and rehabilitation were introduced, and physiotherapists or occupational therapists proposed various trainings suitable for individual subjects if desired.…”
Section: Introductionmentioning
confidence: 99%